The research of the university as a factor increasing its competitiveness - Klyushin, Vladimir; Vasilyeva, Elena; Radchenko, Natalia; Kolpak, Eugeny; Okulova, Larisa (Opción, 2019)
The aim of the study is to investigate the research of the University as a factor increasing its competitiveness via an empirical study, which consisted of a survey of bachelor students of state universities. As a result, most of the respondents agreed that the research activity had a positive impact on the life of the university but did not express a desire to take part in it. In conclusion, to solve this problem, three options were proposed: the popularization of the research activity, expansion of the research activity and cooperation with foreign universities.